The drafting of a proposal of a syllabus to teach B1 level english to the elderly people of the Community of Mejicanos, San Salvador, El Salvador, year 2016 - Meléndez Amaya, Violeta (2024)
Educators dealing with the issue of helping grow up adults to continue their learning, must have a special readiness and preparation to work and develop the appropriate older adult education. They must take into consideration some antecedents about adults who they are going to work with such as how the adults can react in the different learning moments, the experience adults have related the studied field, the needs adults have in that field, and what correct components must be taken into consideration to reach good, effective and as it is possible funny learning with those adults. The research was about how older adults must be treated all the times in the society they belong to, and to find out the suitable drafting of a proposal of a syllabus to teach B1 level English to older adults of the Latter-Day Saints Church Community of the Mejicanos Ward, year 2016. This study sees to find out the suitable components for the course that the Community of the Latter-Saint Church older participants of Mejicanos Ward in San Salvador, El Salvador, year 2016 got as an adequate learning during the 60 hours spent in the Basic1 Level English course, what were the personal characteristics of those older students as participants in the B1 Level English course, and the adequate pedagogical and didactical strategies and activities that were made for those participants to reach a good and useful learning of the basic English language. The study report presents 6 major parts: An Introduction to the situation that lead the researcher to study the problem, a Literature Review that covers the major concepts and issues of the problem, then the Method, next the Results, the Discussion, and six Recommendations.